Тактика допиту при розслідуванні кримінальних проваджень пов’язаних з захопленням заручників - Вигівський, І. М.; Vyhivskyi, I. M. (Прикарпатський юридичний вісник. - 2017. - Вип. 1(16), т. 5, ч. 1.- С. 123-126, 2017)
Розглянуто, що допит потерпілого характеризується тим, що така слідча (розшукова) дія може бути проведена як на початковому, так і на наступному етапі розслідування, в залежності хто саме являється потерпілим. Наголошено на необхідності врахування психологічного стану потерпілого під час допиту. Враховуючи те, що ситуація допиту потерпілого у більшості випадків є конфліктною через його психологічний стан, встановлена можливість використання допиту слідчим суддею під час досудового розслідування, передбаченого ст. 225 КПК України. Наголошено на необхідності участі у допиті потерпілого психолога. Проведено класифікацію допиту потерпілого, в залежності від особи потерпілого, яким може бути як фізична, так і юридична особа. Сформульовано типовий перелік обставин, що підлягають встановленню під час допиту потерпілого.

The scientific article is devoted to the issue of tactics of interrogation of the victim during the pre-trial investigation of criminal proceedings on hostage-taking. Insufficient coverage in the literature of the tactics of interrogation of the victim as a result of hostage-taking has been established. It has been established that the interrogation of a victim is characterized by the fact that such an investigative (search) action can be carried out both at the initial and subsequent stages of the investigation, depending on who the victim is and the psychological state of the victim. Given that the situation of interrogation of the victim in most cases is conflicting, due to his psychological condition, the possibility of using the interrogation by the investigating judge during the pre-trial investigation under Art. 225 of the Criminal Procedure Code of Ukraine. The need to participate in the interrogation of the victim psychologist was emphasized. The interrogation of the victim is classified depending on the person of the victim, which can be both an individual and a legal entity. A typical list of circumstances to be established during the interrogation of the victim is formulated. In cases where the victim of hostage-taking is a child, it is necessary to appoint a forensic psychiatric examination to determine the mental state and the possibility of awareness of the victim committed a criminal offense against him, as well as to determine the veracity of testimony or propensity to fantasize and increased suggestion.

Освещен вопрос тактики допроса потерпевшего во время досудебного расследования уголовного производства связанного с захватом заложников. Подчеркнуто, что допрос потерпевшего характеризуется тем, что такая следственная (сыскная) действие может быть проведена как на начальном, так и на последующем этапе расследования, в зависимости кто именно является потерпевшим. Отмечена необходимость учета психологического состояния пострадавшего во время допроса, а так же необходимость участия в допросе потерпевшего психолога. Проведена классификация допроса потерпевшего, в зависимости от личности потерпевшего, которым может быть как физическое, так и юридическое лицо. Сформулирован типовой перечень обстоятельств, подлежащих установлению в ходе допроса потерпевшего.
Tactics of interrogation in the investigation of criminal proceedings related to hostage-taking
Тактика допроса при расследовании уголовных производств связанных с захватом заложников
Keywords: захоплення заручників; розслідування; кримінальне провадження; допит; потерпілий; hostage-taking; investigation; criminal proceedings; interrogation; victim; захват заложников; расследования; уголовное производство; допрос; пострадавший